Shape stabilized composite phase change materials for thermal energy storage systems / Mohammad Mehrali - Mohammad, Mehrali (2015)
Phase change materials (PCMs) used for the storage of thermal energy as sensible and latent heat are an important class of modern materials which substantially contribute to the efficient use and conservation of waste heat and solar energy. The storage of latent heat provides a greater density of energy storage with a smaller temperature difference between storing and releasing heat than the sensible heat storage method. The main problems with most inorganic PCM materials are their incongruent melting and supercooling effects. Organic PCMs have a high thermal storage capability and also other properties such as good thermal stability and little supercooling but their disadvantage during cooling is their low thermal conductivity below 0.3 W/(m K), which leads to the low heat storage/retrieval rates and low utilization efficiency of the stored energy. This study presents state of the art of shape-stabilized PCMs for thermal energy storage applications and provides an insight into our efforts to develop new shape stabilized PCMs (SSPCMs) with enhanced performance and safety. Specific attention was given to the improvement of thermal conductivity and shape stabilization procedures. In addition, the thermal energy storage properties and performance are discussed for solar energy applications. SSPCMs with nano composite structures have been systematically studied. A series of SSPCMs were fabricated by using the novel carbon nano materials. The carbon nano materials were divided into two groups: graphene materials and porous carbons. The novel graphene materials, including graphene oxide, reduced graphene oxide, nitrogen doped graphene and graphene nanoplatelets were used to prepare novel SSPCMs. The porous carbons like carbon nanospheres and activated carbon also were employed to prepare other SSPCMs. The structural, morphological and thermal features of the newly developed SSPCMs were evaluated by a series of modern instruments and characterization technologies, including DSC, TGA, FT-IR, Raman spectroscopy, TEM, SEM, XRD and LFA. The thermal reliability of prepared SSPCMs was investigated using a thermal cycler for a large number of heating and cooling process. In this research, a novel type of SSPCMs by using graphene materials have shown excellent multifunctional thermal properties and thermal stabilities that are far beyond those of the conventional SSPCMs. The graphene materials have shown better performance compare to the porous carbons. The novel SSPCMs can be used to develop advanced smart materials and products with prosperous and promising applications in a number of industries.